Phytotoxicity of sewage sludge from selected wastewater treatment plants - new opportunities in sewage sludge treatment - Ondřej Šindelá; Dana Adamcová; Jan Zloch; Magdalena Daria Vaverková (International Journal of Recycling of Organic Waste in Agriculture, 2020)
Purpose The research was focused on evaluating phytotoxicity of sewage sludge from two selected wastewater treatment plants in Czech Republic. Methods Laboratory experiments were carried out with samples of sewage sludge, which were focused on the evaluation of their phytotoxicity by using the PhytotoxkitTM testing set. Specifically, the inhibitory/stimulating effect was established on the growth of roots from the seeds of white mustard (Sinapis alba L.). The chosen proportions of sewage sludge were 10%, 30% and 50%. The test was conducted in three repetitions. Additionally, the research also included a comparison of the effect of compost addition to the sewage sludge and its potentially increased stimulating effect on the growth of roots from the seeds of white mustard (Sinapis alba L.). Ratios of compost were 5%, 15%, 25% and 50%. The test was conducted in three repetitions. Results Stimulating effect on the growth of white mustard (Sinapis alba L.) was demonstrated only in samples with the sludge proportion of 10%. The results also show that the addition of compost reduced phytotoxicity of sewage sludge in all three tested ratios (5%, 15%, 25% and 50%). Conclusion It was found out that the addition of compost resulted in the decreased phytotoxicity of all tested sewage sludge samples, and hence in their suppressed inhibitory effect.